An antihypertensive agent benidipine is an effective neuroprotective and antiepileptic agent: an experimental rat study. (2nd December 2021) - Koçak, Mehmet Nuri; Arslan, Remzi; Albayrak, Abdulmecit; Tekin, Erdal; Bayraktar, Mustafa; Çelik, Muhammet; Kaya, Zülküf; Bekmez, Hüseyin; Tavaci, Taha
ABSTRACT: Background: Benidipine is an L, N and T type calcium channel blocker drug that is widely used as an antihypertensive drug. Objective: For the first time in the literature, it was aimed to investigate the effectiveness of benidipine in controlling epileptic seizure and preventing the development of neurodegeneration in epilepsy. Methods: An experimentally epilepsy model was produced with pentylenetetrazole, and rats were divided into seven groups, in different benidipine treatment doses or with valproic acid combinations. The epileptic activities of all rats were recorded according to the Fisher&Kittner classification. Biochemical parameters, histopathological Caspase-3 activity, Wyler hippocampal sclerosis, gliosis and neuronal degenerations were investigated. Results: It was found that in the post-hoc analysis of epileptic activities, there was a similar antiepileptic scores among the treatment groups. IL-1 level was found to be significantly lower in the benidipine 4 mg/kg group, and TNF-alpha was lower in the group given valproic acid+benidipine 2 mg/kg (p<0.05). The other biochemical parameters were not found to be significant. Neural degeneration levels in the brain tissues were statistically significant (p<0.001). Compared with the healthy group, the most neural degeneration was in the control group, the least neural degeneration was in the valproic acid+benidipine 4 mg/kg group. Conclusions: For the first time in the literature, benidipine, alone or combined with valproic acid, were found to have a statistically significant antiepileptic efficacy, and provided neuroprotection when combined with valproic acid. Benidipine will be a promising agent in the treatment of epilepsy with its antiepileptic and neuroprotective effects.